2018
DOI: 10.1002/jcb.27881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phospholipase D during cultured osteoblast mineralization and bone formation

Abstract: Mammalian phospholipase D (PLD) mostly hydrolyzes phosphatidylcholine producing phosphatidic acid. PLD activity was previously detected in different osteoblastic cell models, and was increased by several growth factors involved in bone homeostasis. To confirm possible actions of PLD isoforms during mineralization process, we analyzed their effects in osteoblastic cell models and during bone formation. PLD1 expression, along with PLD activity, increased during differentiation of primary osteoblasts and Saos‐2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…30 Abdallah et al evaluated the phospholipase D on the mineralization of osteoblasts. 31 The alizarin red staining method was also used to evaluate the differentiation and osteogenic ability of osteoblasts. In this study, after 7 days of induced mineralization, alizarin red staining confirmed that C3G has a positive regulatory effect on the mineralization ability of osteoblasts, and C3G treatment can increase mineralization in cell slides in a dose-dependent manner.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Abdallah et al evaluated the phospholipase D on the mineralization of osteoblasts. 31 The alizarin red staining method was also used to evaluate the differentiation and osteogenic ability of osteoblasts. In this study, after 7 days of induced mineralization, alizarin red staining confirmed that C3G has a positive regulatory effect on the mineralization ability of osteoblasts, and C3G treatment can increase mineralization in cell slides in a dose-dependent manner.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Both et al stained osteoblast-mineralized nodules using alizarin red dye in a study of hydroxychloroquine, inhibiting osteoblast mineralization . Abdallah et al evaluated the phospholipase D on the mineralization of osteoblasts . The alizarin red staining method was also used to evaluate the differentiation and osteogenic ability of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway enrichment analysis was performed to determine the dominant phenomenon ongoing in each fraction (Figure S1). The genes reduced in the 50/70 fraction compared with the 10/30 fraction included the pathways involved in the immature state, such as “hippo signaling pathways” and “pathways regulating pluripotency of stem cells.” 26,27 In contrast, genes upregulated in the 50/70 cell fraction compared with the 10/30 fraction were enriched in pathways involved in osteoblast differentiation, such as “osteoclasts,” “phospholipase D signaling,” and “lysosome.” 28,29 …”
Section: Resultsmentioning
confidence: 99%
“…26,27 In contrast, genes upregulated in the 50/70 cell fraction compared with the 10/30 fraction were enriched in pathways involved in osteoblast differentiation, such as "osteoclasts," "phospholipase D signaling," and "lysosome." 28,29…”
Section: Comprehensive Microarray Analysis Of Gene Expression Pattern In the Three Fractionsmentioning
confidence: 99%
“… 134 PLD releases lysophosphatidic acid, an important signalling molecule capable of enhancing procalcifying genes, 135 and also promotes mineralization. 136 …”
Section: Sources Of Phosphatementioning
confidence: 99%